2021
DOI: 10.21203/rs.3.rs-147899/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape Characteristics Influence Ranging Behavior of Asian Elephants at the Human-wildlands Interface in Myanmar

Abstract: Context Asian elephant numbers are declining across much of their range, driven largely by serious threats from land use change resulting in habitat loss and fragmentation. Myanmar, holding critical range for the species, is undergoing major developments due to recent sociopolitical changes. To effectively manage and conserve the remaining populations of endangered elephants in the country, it is crucial to understand their ranging behavior.Objectives Our objectives were to (1) quantify dry season range sizes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Wild African elephants are reported to walk 3 to 12 km per day under normal environmental conditions [ 39 , 40 , 41 , 95 ], and can range up to 27 km per day or more for landscape-level movements such as seasonal migrations or dispersal [ 96 ] or under extreme conditions such as in water scarce regions of Namibia [ 31 , 97 , 98 ]. By contrast, wild Asian elephants in Myanmar were shown to walk from 1.3 to 7.3 km per day [ 99 ]; in Sri Lanka, shorter daily walking distances were found in elephant groups with nursing calves (1 to 3.5 km) or juveniles (3 to 8.5 km) [ 62 ], as cited in [ 38 ]. Another measurement of movement is distance displaced, which measures a straight-line change in location as a result of walking any pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild African elephants are reported to walk 3 to 12 km per day under normal environmental conditions [ 39 , 40 , 41 , 95 ], and can range up to 27 km per day or more for landscape-level movements such as seasonal migrations or dispersal [ 96 ] or under extreme conditions such as in water scarce regions of Namibia [ 31 , 97 , 98 ]. By contrast, wild Asian elephants in Myanmar were shown to walk from 1.3 to 7.3 km per day [ 99 ]; in Sri Lanka, shorter daily walking distances were found in elephant groups with nursing calves (1 to 3.5 km) or juveniles (3 to 8.5 km) [ 62 ], as cited in [ 38 ]. Another measurement of movement is distance displaced, which measures a straight-line change in location as a result of walking any pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Food and water availability have been shown to influence walking distance in free-ranging Asian elephants [ 99 , 100 ], and thus one of the challenges in a zoo setting is to encourage walking given ample food provisions. Holdgate et al [ 37 ] found individual differences in walking distances associated with demographic, social, housing, and feeding-related variables.…”
Section: Discussionmentioning
confidence: 99%